Political Challenges of Institution Building (Kurdistan Region as a Model) - Jamil, ئاراسن; ئەحمەد, زوبێر (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
The aim of this research paper is to investigate the political challenges of institution building in the Kurdistan Region and answer the question of what factors have hindered the process of institution building in the Kurdistan Region as a post-war society after 1991. Are these internal or external factors affecting the process of institution building in the Kurdistan Region? However, we believe that in this research paper, both factors hinder the rebuilding of institutions in the Kurdistan Region. Unlike other studies that see one factor as more effective, we pay attention to any problem that becomes an obstacle to the rebuilding of institutions. For example, (the conflict between components and armed forces, the dominance of the party in the government, and the problem of citizens’ lack of trust in institutions), destroyed the building of institutions in the Kurdistan Region.